Pengungkapan Tanggung Jawab Sosial Perusahaan dan Economic Value Added: Peranan Moderasi Kepemilikan Keluarga dan CSR Award - Herni Kurniawati; Yvonne Augustine Sudibyo (STIE Indonesia Banking School, 2017)
The aim of this research was to create an index of corporate social responsibility disclosure based on SDGs and to see its impact on corporate economic value added with family companies and CSR rewards as a moderating variable. This research is a causal research to examine the influence of corporate social responsibility disclosure to economic value added which is moderated by family company characteristic and CSR award in manufacturing company listed in Indonesia Stock Exchange. The disclosure of corporate social responsibility based on the global standards of SDGs shows that there is no added value for companies reporting their social responsibilities despite being moderated by family firms and Corporate Social Responsibility Award received by companies.From the result of the research, it can be concluded that companies in Indonesia whether it is manufacturing or non-manufacturing whose operations give effect to the surrounding environment, better implement the SDGs as a global standard in expressing social responsibility activities to attract investors, especially foreign investors (European countries). The reason is that companies in European countries already widely apply the SDGs as a global standard in reporting its social responsibility. This is in line with the UN decision to implement SDGs as a standard of social responsibility reporting for companies in developed and developing countries which took effect from 2015 ago.